Plastic diet: An effort to overcome the problem of plastic waste in Cipayung Village, Depok, West Java - Utari, Dyah; Fitri, Azizah Musliha; Maharani, Fandita Tonyka (Community Empowerment)
Cipayung Village is an area of the Final Disposal Site (FDS) of Depok City. With the FDS, it will automatically have an impact on the surrounding community, coupled with the daily pattern of people who are accustomed to using plastic materials such as shopping containers. This results in more plastic waste in Cipayung Village. This problem requires real action that can make people aware to reduce plastic waste. The plastic diet is a campaign to the community in RT RW Cipayung Village which aims to increase public awareness of the dangers of plastic waste. This activity was carried out by distributing leaflets, reusable shopping bags, and educating the public. The results obtained from this activity are an increase in public knowledge about the dangers of plastic waste and a change in the habit of using plastic bags into shopping bags that can be used repeatedly. This behavior change significantly reduces the use of plastic bags in Cipayung Village. It is hoped that this activity will not only be carried out in one RT but can be carried out in other locations.